Pubertal stage, body mass index, and cardiometabolic risk in children and adolescents in Bogotá, Colombia: The cross-sectional fuprecol study (2017)
This study explored the association between pubertal stage and anthropometric and cardiometabolic risk factors in youth. A cross-sectional study was conducted in 2877 Colombian children and adolescents (9–17.9 years of age). Weight, height, and waist circumference were measured and body mass index (BMI) was calculated. A biochemical study was performed to determine the cardiometabolic risk index (CMRI). Blood pressure was evaluated and pubertal stage was assessed with the Tanner criteria. Hierarchical multiple regression analyses were performed. The most significant variable (p less than 0.05) in the prognosis of cardiometabolic risk was found to be the BMI in both boys and girls. In the case of girls, the pubertal stage was also a CMRI predictive factor. In conclusion, BMI was an important indicator of cardiovascular risk in both sexes. Pubertal stage was associated with cardiovascular risk only in the girls. © 2017 by the authors. Licensee MDPI, Basel, Switzerland.